The Chinese cinema book - Lim, Song Hwee; Ward, Julian (Palgrave Macmillan, 2011)
Introduction: the Coming of Age of Chinese Cinemas Studies / Song Hwee Lim and Julian Ward -- Territories, Trajectories, Historiographies. Transnational Chinese Cinema Studies / Chris Berry -- National Cinema as Translocal Practice: Reflections on Chinese Film Historiography / Yingjin Zhang -- Cinemas of the Chinese Diaspora / Gina Marchetti -- Six Chinese Cinemas in Search of a Historiography / Song Hwee Lim -- Early Cinema to 1949. Shadow Magic and the Early History of Film Exhibition in China / Xuelei Huang and Zhiwei Xiao -- The Making of a National Cinema: Shanghai Films of the 1930s / Laikwan Pang -- Wartime Cinema: Reconfiguration and Border Navigation / Yiman Wang -- Chinese Film-making on the Eve of the Communist Revolution / Paul G. Pickowicz -- The Forgotten Period: 1949-80. The Remodelling of a National Cinema: Chinese Films of the 17 Years (1949-66) / Julian Ward -- Healthy Realism in Taiwan, 1964-80: Film Style, Cultural Policies, and Mandarin Cinema / Guo-Juin Hong -- The Hong Kong Cantonese Cinema: Emergence, Development and Decline / Stephen Teo -- The New Waves. The Fifth Generation: a Re-assessment / Wendy Larson -- Taiwan New Cinema and Its Legacy / Tonglin Lu -- The Hong Kong New Wave: A Critical Reappraisal / Vivian P. Y. Lee -- Stars, Auteurs and Genres. Dragons Forever: Chinese Martial Arts Stars / Leon Hunt -- The Contemporary Wuxia Revival: Genre Remaking and the Hollywood Transnational Factor / Kenneth Chan -- On the Shoulders of Giants: Tsai Ming-liang, Jia Zhangke, Fruit Chan and the Struggles of Second Generation Auteurism / James Udden -- The Urban Generation: Underground and Independent Films from the PRC / Jason McGrath -- Contemporary Mainstream PRC Cinema / Yomi Braester -- Contemporary Meta Chinese Film Stardom and Transnational Transmedia Celebrity / Anne Ciecko -- Afterword: Liquidity of Being / Rey Chow
Includes bibliographical references and index -- Includes filmography
Keywords: Aufsatzsammlung; Film; China